Can Poductive Government Spending be the Engine of Long-Run Growth When Labor Supply is Engogenous? - Hyun Park; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2002)
We reexamine the properties of optimal fiscal policy and their implications for implementable capital accumulation. The setup is a standard endogenous growth model with public production services, augmented by elastic labor supply. We show that, when a benevolent government chooses a distorting income tax rate to finance public production services by taking into account the competitive decentralized equilibrium, public production services can no longer play their traditional role as an engine of long-run endogenous growth. This follows from a simple combination of Ramsey second-best fiscal policy and endogenous labor/leisure choices.
Keywords: 330; second-best policy; elastic labor supply; endogenous growth